Optimization design of an EWMA-p chart - Verdyka Kurniawan (2010)
Nowadays, quality has become the most important factor of consumer purchasing decision. It determines how competitive a product is in the market. Consequently, industry is also focusing on how to maintain and improve quality. The statistical process control is developed to enhance quality improvement. One of the techniques of statistical process control is the control chart. The Exponentially Weighted Moving Average-p (EWMA) chart for attribute quality characteristic is studied in this project. This chart is useful in detecting small or moderate shifts in the process. The EWMA-p Chart is an effective tool for monitoring an attribute of quality characteristics. In this project, the optimization design of the EWMA-p chart was carried out. Its performance and effectiveness were evaluated and compared with that of a Conventional EWMA-p Chart. In general, the optimization design procedure consists of calculating the desired in-control and out-of-control average run lengths and the process shifts that is anticipated, and then to choose the combination value of λ and H(control limit) that provide the desired ARL performance and minimum loss.